Skills and abilities for working in a global software development team: a competence model. Issue 3 (25th February 2013) - Saldaña‐Ramos, Javier; Sanz‐Esteban, Ana; García, Javier; Amescua, Antonio; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT Nowadays, it is common to develop software development projects collaboratively among team members or organizations in different geographical locations. These teams, known as global software development (GSD) teams, allow organizations to save costs as well as have available highly qualified personnel. This kind of team is different from traditional teams, so it is necessary for team members to develop other essential competences to work efficiently in a global context. Unfortunately, there is no well‐defined competence model that allows organizations to assess personnel competences and establish the relevant training program that allows them to work efficiently in such teams. This work defines and implements, in four GSD teams, a competence model specifically designed to address challenges that people face when they work in a GSD team. This competence model has been defined considering tasks a GSD team have to carry out, bodies of knowledge, and existing competence models for the software engineering profiles and the authors' experience working in such teams. As a result of the implementation process, it was confirmed that the competence model is a key factor for human capital improvement. When personnel have these competences, team and individual efficiency and product quality increase, and delays in delivering products decrease. Copyright © 2013 John Wiley & Sons, Ltd.